Effects of oleanolic acid on inflammation and metabolism in diabetic rats. (19th May 2022) - Iskender, Hatice; Dokumacioglu, Eda; Terim Kapakin, Kubra Asena; Yenice, Guler; Mohtare, Behzat; Bolat, Ismail; Hayirli, Armagan
ABSTRACT: Diabetes mellitus (DM) is a chronic metabolic disease that threatens the health of the world population. We investigated the effects of oleanolic acid (OA) administration on inflammation status and metabolic profile in streptozotocin (STZ) induced diabetic rats. Four experimental groups were established: healthy rats not administered OA, healthy rats administered OA, diabetic rats not administered OA, diabetic rats administered OA. OA, 5 mg/kg, was administered by oral gavage for 21 days. Serum samples collected at the end of the experiment and analyzed for toll–like receptor–9, interleukin-18, nuclear factor kappa B, malondialdehyde MDA, glucose, total cholesterol, triglycerides, high–density lipoprotein, low-density lipoprotein, calcium, phosphorus, magnesium and potassium. Pancreas tissue was examined for pathology. Induction of DM caused increased serum concentrations of inflammation and oxidative damage markers. DM also caused hyperglycemia-hyperlipidemia and decreased serum concentration of minerals. The islets of Langerhans were degenerated and necrotic. Administration of OA reversed the adverse effects of DM. OA treatment can ameliorate inflammation and oxidative damage due to DM by normalizing hyperglycemia and decreasing TLR-9, IL-18, NF-κB and MDA levels.